The underlying structure of visuospatial working memory in children with mathematical learning disability - Mammarella, Irene C.; Caviola, Sara; Giofrè, David; Szűcs, Dénes (British journal of developmental psychology, 2018)
This study examined visual, spatial‐sequential, and spatial‐simultaneous working memory (WM) performance in children with mathematical learning disability (MLD) and low mathematics achievement (LMA) compared with typically developing (TD) children. Groups were matched on reading decoding performance and verbal intelligence. Besides statistical significance testing, we used bootstrap confidence interval estimation and computed effect sizes. Children were individually tested with six computerized tasks, two for each visuospatial WM subcomponent. We found that both MLD and LMA children had low visuospatial WM function in both spatial‐simultaneous and spatial‐sequential WM tasks. The WM deficit was most expressed in MLD children and less in LMA children. This suggests that WM scores are distributed along a continuum with TD children achieving top scores and MLD children achieving low scores. The theoretical and practical significance of findings is discussed. Statement of Contribution What is already known on this subject? Working memory plays an important role in mathematical achievement. Children with mathematical learning disability (MLD) usually have low working memory resources. Conflicting results have been reported concerning the role of VSWM in individuals with MLD. What the present study adds? Children with different degree of impairment in math achievement and typically developing children were tested. Visual, spatial‐sequential, and spatial‐simultaneous working memory tasks were examined. Only spatial‐sequential and spatial‐simultaneous working memory tasks discriminated the two impairments groups.